Sustainability of Four Dairy Farming Scenarios in an Alpine Environment: The Case Study of Toma di Lanzo Cheese - Verduna, Tibor; Blanc, Simone; Merlino, Valentina Maria; Cornale, Paolo; Battaglini, Luca Maria (Frontiers in Veterinary Science, 2020)
The dairy sector accounts for a large share of all European agricultural production, at the same time however, it is one of the most ascribed sector contributors to the environmental impact of agriculture, particularly for greenhouse gas emissions. Simultaneously, it is a strategic sector for the economy but generates increasing debate in the community regarding the social aspects mainly related to the use of resources and the food-feed competition of livestock involving the reduction of human-edible crops. In this general framework, this study aims to compare four different dairy farming scenarios characterized by different use of environmental resources in the Alpine area, considering as a case study the production of the Toma di Lanzo cheese (a traditional cheese produced in the mountainous regions of Piedmont – Northwest Italy). The study envisaged the integrated use of three methodologies: Life Cycle Assessment, Life Cycle Costing and the assessment of human-edible feed conversion efficiency to jointly analyze environmental, economic and social aspects. The main results of this research highlighted how the utilization of local breeds, which maximize the efficiency in the use of territory resources, such as grasslands in a mountain environment, allowed dairy production to reduce emissions, when compared to the high-input traditional breeding systems. Although the mountain livestock systems have several critical issues mainly linked to social factors such as low generational turnover, work schedules, modest life quality of families, it is however possible to earn more income than in lowland scenarios. At the same time, this production system allows the Toma di Lanzo cheese-making heritage to be preserved. This mountain pasture cheese, to which superior organoleptic and nutritional characteristics are attributable, when compared to cheeses from the valley floor, incorporates traditional values, a link to the territory and the transmission of knowledge. With reference to food-feed competition in livestock involving the reduction of the use of human-edible crops and feedstuffs in animal diets, we found that grazing and grass-based feeding systems were one of the most sustainable ways to produce milk.